Critical path analysis of TCP transactions. - Barford, Paul (Computer communication review.)
Improving the performance of data transfers in the Internet (such as Web transfers) requires a detailed understanding of when and how delays are introduced. Unfortunately, the complexity of data transfers like those using HTTP is great enough that identifying the precise causes of delays is difficult. In this paper we describe a method for pinpointing where delays are introduced into applications like HTTP by using critical path analysis. By constructing and profiling the critical path, it is possible to determine what fraction of total transfer latency is due to packet propagation, network variation (e.g., queuing at routers or route fluctuation), packet losses, and delays at the server and at the client. We have implemented our technique in a tool called tcpeval that automates critical path analysis for Web transactions. We show that our analysis method is robust enough to analyze traces taken for two different TCP implementations (Linux and FreeBSD). To demonstrate the utility of our approach, we present the results of critical path analysis for a set of Web transactions taken over 14 days under a variety of server and network conditions. The results show that critical path analysis can shed considerable light on the causes of delays in Web transfers, and can expose subtleties in the behavior of the entire end-to-end system.